Online Eye-gaze Usability Evaluation of Gmail: Are mobile interfaces easier to use with eye-trackers? - Chen, Caroline Wenjia; Hennessey, Craig (CMBES Proceedings, 2010)
Eye tracking can be used as an assistive technology allowing users to control the cursor with their eyes, enabling web browsing and sending emails hands-free. Eye-gaze for web browsing is not an easy task, and users are typically the disabled who cannot use the standard computer mouse and keyboard. The lower accuracy and reliability of eye-gaze make targeting lines on web pages more difficult. Increasingly, web content is being offered in “mobile” or small screen formats for devices such as the iPhone. In this paper we will investigate the potential increase in usability of “mobile” web pages over standard web pages when using eye-gaze as the web interface mechanism. The mobile application under evaluation is Google Gmail, and the eye-gaze tracking system is the Mirametrix S1 eye-tracker and Passport communication tool. How people use eye-tracking to send emails through Gmail will be compared under three conditions, standard keyboard and mouse, eye-tracking on standard Gmail and eye-tracking on mobile Gmail. The evaluation metrics are efficiency (quantitative speed) and ease of use (qualitative user opinions). The usability evaluation presented in this paper will provide an indication on whether mobile formatted websites are easier to use than standard web pages when eye-gaze is used as the interface. This paper will also suggest a number of potential design improvements for web content when used with eye-tracking devices.